Systematic Review: Leadership Style in Maintaining Business Sustainability in the MSME Industry - Aristayudha, A A Ngurah Bagus; Riana, I Gede; Rahyuda, Agoes Ganesha; Surya, Ida Bagus Ketut (Journal of Economics and Public Health, 2023)
Leadership style is the way a leader chooses to direct or coordinate the work that will be given to his subordinates. The leadership style chosen by a leader depends on the goals of the organization or company, who is being led, and the type of business led by the leader. Systematic review using the Google Scholar database. Search results using the keyword leadership style in maintaining business continuity in the MSME industry" using the Google Scholar electronic data base. After carrying out an analysis based on a complete composition, namely 5 articles used in this article. The results of this research show that there are many types of leadership styles, but the choice of leadership style depends on the situation and conditions of the organization or business being led. The types of leadership styles include democratic leadership style, authoritarian leadership style and leadership styles that are appropriate to current conditions, namely transactional and transformational. MSMEs are a type of small business that also requires a leadership style that is appropriate to the type of business and the goals of the business to maintain the stability or sustainability of the business. Leadership style is a method or tactic used by a leader to direct and coordinate activities in an organization so that organizational goals are expected to be achieved.